Behaviour Analysis of DDoS Attack and Its Detection - Mahadev,; Kumar, Vinod (International Journal of Computer Sciences and Engineering, 2025)
In recent times the internet is growing exponentially. Many important services and records are available on different websites of the government and as well as of private sectors. A valid user becomes irritated when websites become unavailable when needed. Human being accesses only those web pages in which they are interested in. Some flash crowd occurs on specific time or events. Attacker’s main aim is not to browse specific web pages of valid users’ interest but to fail the web server so that authentic users could not avail web services. The DDoS attack becomes difficult to detect when this attack imitates the behaviour of irritating and non-professional users. There is need to analyze the behaviour of sophisticated DDoS attacks using advanced tools of DDoS attack at Layer 7. This paper analyzes tool of DDoS attacks using their log records and checks behaviour of DDoS attacks and stores its pattern in ODAM (One Dimensional Access Matrix). It also proposes an efficient algorithm to detect DDoS attacks at the application layer.